The present and the future of motif-mediated protein-protein interactions - Seo, Moon-Hyeong; Kim, Philip M. (CURRENT BIOLOGY LTD, 2018)
Protein protein interactions (PPIs) are essential to governing virtually all cellular processes. Of particular importance are the versatile motif-mediated interactions (MMIs), which are thus far underrepresented in available interaction data. This is largely due to technical difficulties inherent in the properties of MMIs, but due to the increasing recognition of the vital roles of MMIs in biology, several systematic approaches have recently been developed to detect novel MMIs. Consequently, rapidly growing numbers of motifs are being identified and pursued further for therapeutic applications. In this review, we discuss the current understanding on the diverse functions and disease-relevance of MMIs, the key methodologies for detection of MMIs, and the potential of MMIs for drug development.
Keywords: SHORT LINEAR MOTIFS; INTRINSICALLY DISORDERED REGIONS; PEPTIDE RECOGNITION MODULES; STRUCTURAL BASIS; POSTTRANSLATIONAL MODIFICATION; CELL REGULATION; YEAST 2-HYBRID; SPOT-SYNTHESIS; DOMAIN FAMILY; PHAGE DISPLAY